Pendampingan Pemasaran Digital Marketing Tas Anyaman Melalui Media Sosial Facebook Di Desa Prajegan Sukorejo Ponorogo - Sari, Ratna; Asfahani, Asfahani; Fikriawan, Suad (Social Science Academic, 2024)
This study aims to assist basketry craftsmen in Prajegan Village, Sukorejo, Ponorogo, in utilizing Facebook as a marketing tool to increase their product sales. Using the Asset-Based Community Development (ABCD) method, the research identifies local strengths and assets as the foundation for developing a digital marketing strategy. Intensive training and mentoring were provided to enhance the craftsmen's digital skills, particularly in managing Facebook as a promotional platform. The results indicate that this mentoring successfully improved the craftsmen's ability to use Facebook effectively, leading to a significant increase in their product sales. The implementation of this method demonstrates that an asset-based approach and tailored training can empower communities and support the sustainability of small businesses.